Communication in the Digital Work Environment: Implications for Wellbeing at Work - Bordi, Laura; Okkonen, Jussi; Mäkiniemi, Jaana-Piia; Heikkilä-Tammi, Kirsi (Nordic Journal of Working Life Studies, 2018)
This article examines digital communication in the workplace and its association with wellbeing at work. The analysis is based mainly on workshop discussions and is complemented with log data (N = 36). Content analysis was applied to the workshop discussions, while the log data were analyzed by quantifying frequencies. Six themes were found to affect wellbeing at work: the volume of digital communication, expectations of constant connectivity, the quality of the messages, adaptation of new tools, technical problems, and flexibility in communication. In relation to wellbeing at work, digital communication was mostly perceived as demanding. However, some of the factors perceived as demanding could also provide flexibility, which was seen as enhancing wellbeing by increasing autonomy and control. Social factors, such as work habits, practices, and conventions in the workplace, seem to play an important role in the manifestation and management of the digital communication-induced load at work.